Quantitative history of society and economy: some international studies - Jarausch, Konrad; Schröder, Wilhelm H. (1987)
Abstract: Contents: I. The State of the Debate - Konrad H. Jarausch: (Inter-)national Styles of Quantitative History (5-18); Charles Tilly: Formalization and Quantification in Historical Analysis (19-29); Heinrich Best, Wilhelm Heinz Schröder: Quantitative Historical Social Research: The German Experience (48). II. Social Inequality in Comparative Perspective - Hartmut Kaelble: Social Inequality in the 19th and 20th Centuries: Some Introductory Remarks (49-57); Johan Söderberg: Trends in Inequality in Sweden, 1700-1914 (58-78); Olivier Zunz: The Collar Line: Clerical Workers in America at the Turn of the Century (79-93); Janusz Zarnowski: Social Inequalities in 20th Century Poland (94-112). III. Economic, Social, and Political Transitions - Patrice Bourdelais: Transitions from Agricultural to Industrial Societies: Some Introductory Remarks (113-119); John Komlos: Patterns of Children's Growth in East-Central Europe in the Eighteenth Century (120-141); Fausto Dopico: The Transformation of Spa